The Physical Volume of Production in the United States for 1923 - Day, Edmund E. (The Review of Economics and Statistics, 1924)
HE true proportions of current economic movements are rarely discernible until the movements are viewed in retrospect. The physical volume of production in I923 is a case in point. During the year it was realized, of course, that current output was large, but it was not generally recognized that a new high record for physical production was being set. The high level of output in I923 is most conveniently summarized in index numbers of the physical volume of production. Indexes of this kind are available for the five major divisions of industry: agriculture, animal husbandry, forestry, mining, and manufacture. The indexes for the years I9I9-23 are given in Table A.